2008 Design, Automation and Test in Europe 2008
DOI: 10.1109/date.2008.4484754
|View full text |Cite
|
Sign up to set email alerts
|

Random Stimulus Generation using Entropy and XOR Constraints

Abstract: Despite the growing research effort in formal verification, constraint-based

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…In [11], it is shown that if S f is the set of all solutions of f , then the addition of constraints from k such random w vectors probabilistically reduces the solution space to 2 −k |S f |.…”
Section: Deriving Evenly-distributed Sat Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [11], it is shown that if S f is the set of all solutions of f , then the addition of constraints from k such random w vectors probabilistically reduces the solution space to 2 −k |S f |.…”
Section: Deriving Evenly-distributed Sat Solutionsmentioning
confidence: 99%
“…Based on the Valiant-Vazirani theorem [13], Plaza et al [11] proposed to use XOR-constraints to generate SAT solutions that are evenly distributed. In their technique, assume that a SAT instance f with variables x 1 , x 2 , .…”
Section: Deriving Evenly-distributed Sat Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the verification and validation of large design components constraint-based random simulation remains an integral part. In [18] entropy metrics to define coverage targets of internal signals is combined with a framework which uses small randomized XOR constraints to generate stimuli for inadequately stimulated circuit regions. The authors in [19] present a methodology to analyze contradictory constraints that occur in constraint-based random simulation.…”
Section: Related Workmentioning
confidence: 99%
“…There exist several studies focusing on both pattern generation speed and distribution evenness [2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%